Preparation method and application of fiber reinforced autoclaved aerated concrete board

By using fibers to replace the steel bars in the autoclaved aerated concrete slab and combining them with active excitants, the problems of uneven gas layer, uneven stress distribution and insufficient durability caused by the steel bars in the prior art are solved, and higher compression, bending, crack resistance and lower maintenance costs are achieved.

CN119430839BActive Publication Date: 2025-03-28CHINA RAILWAY URBAN CONSTR GRP CONSTR TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510045974.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-28
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

During the manufacturing process, existing autoclaved aerated concrete slabs with built-in steel bars have uneven gas layer, uneven stress distribution, and increased risk of damage due to the difference in thermal expansion coefficient between the steel bars and the slurry; during construction and use, it is prone to cracking, insufficient durability and stability; it is prone to rust and cracking during cutting of steel bars, affecting safety and service life; it is prone to mildew and alkaline in high humidity environments, increasing maintenance costs.

Method used

The structural steel bars are replaced by fibers. Through the combination of fibers and active excitants, the concrete slurry is more uniformly air-emitting. The fibers are evenly distributed by multi-stage dispersion, which improves bending, compressive, and cracking properties, and enhances anti-mold and anti-alkali properties.

Benefits of technology

It improves the slab formation rate and production efficiency of concrete slabs, reduces costs and waste materials, significantly improves product quality and compressive, bending and crack resistance, extends service life, and reduces later maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430839B_ABST
    Figure CN119430839B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete slabs, and specifically discloses a method for preparing a fiber-reinforced autoclaved aerated concrete slab and an application thereof. The method comprises: preparing pretreated raw materials according to a formula; distributing and mixing the raw materials uniformly, and obtaining slurry one, slurry two and slurry three in sequence; pouring slurry three into a mold and then curing; demoulding and cutting a blank; preparing a finished concrete slab after steaming and cooling the blank after cutting; using fibers to replace structural steel bars, saving steel bar usage, so that steel bar corrosion will not be caused by cutting, thereby improving the slab yield and production efficiency, avoiding waste of waste materials, and improving the actual preparation efficiency; secondly, using fibers and active stimulants, making the concrete slurry gassing more uniform, and using a multi-stage dispersion method to make the fibers uniformly distributed, effectively improving the bending resistance, compression resistance, crack resistance, nail holding force, mildew resistance and anti-eluviation performance of the concrete slab, and significantly improving product quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of concrete slabs, and more specifically, relates to a preparation method of a fiber reinforced autoclaved aerated concrete slab and an application thereof. Background Art

[0002] Traditionally, the walls of residential buildings mainly rely on traditional block materials such as red bricks. These materials are not only costly and limited in strength, but also have low construction efficiency. At the same time, they consume a lot of energy during production and use, and cause certain pollution to the environment. With the advancement of science and technology, a variety of new interior wall panels have emerged in the domestic market, such as glass fiber reinforced cement lightweight panels, fiber cement boards, autoclaved aerated concrete panels (ALC), lightweight aggregate concrete panels, wire mesh sandwich panels, gypsum boards, metal panel sandwich panels, and composite wall panels. Among these new partition wall materials, ALC panels stand out with their excellent performance and become the mainstream choice, occupying more than 60% of the market share of non-masonry applications of partition walls.

[0003] The autoclaved aerated concrete board uses cement, fly ash, aluminum powder, lime and silica sand as the main components, and is equipped with rust-proof steel bars to enhance the structural stability. This board is manufactured under high temperature and high pressure steam curing conditions to form a lightweight and porous concrete product. In the prior art, a Chinese patent with publication number CN215167134U discloses an autoclaved aerated concrete board with built-in truss steel bars, including an autoclaved aerated concrete layer and two layers of steel mesh, the two layers of steel mesh are arranged in parallel and at intervals in the autoclaved aerated concrete layer, and the autoclaved aerated concrete layer is also provided with two groups of truss steel bars, the two groups of truss steel bars are arranged in parallel between the two layers of steel mesh and along the long sides of the steel mesh, and the two layers of steel mesh are fixed to the truss steel bars on both sides; the autoclaved aerated concrete layer is also provided with two groups of steel plate profiles, the two groups of steel plate profiles are arranged in parallel between the two layers of steel mesh and along the short sides of the steel mesh, and the two layers of steel mesh are fixed to the steel plate profiles on both sides.

[0004] The above patent can increase the tensile properties of autoclaved aerated concrete slabs without increasing the cross-sectional area of ​​the reinforcement and setting up a steel mesh cage, and the production cost is low; the truss steel bars and steel plate profiles are located at the edge of the autoclaved aerated concrete layer, avoiding collision damage to weak parts. However, it still does not solve some problems of existing ALC panels with built-in steel bars: (1) Steel bars must be added during the manufacturing process of ALC panels to enhance structural stability, which not only increases material costs, but also easily leads to the formation of gas layers due to the difference in thermal expansion coefficients between steel bars and slurry. This uneven gas generation phenomenon will cause uneven stress distribution inside the blank, thereby increasing the risk of plate damage and affecting the overall quality. (2) Due to the high porosity inside the ALC panels, they are prone to cracking due to rapid evaporation of water during maintenance. At the same time, the large thermal shrinkage characteristics of the steel mesh further increase the possibility of cracks, weakening the durability and stability of the panels. (3) ALC panels with added steel bars are not easy to groove and cut during construction, and the anti-rust coating on the surface of the steel bars will be destroyed during the cutting process, exposing the steel bars to the air and making them easy to rust. In addition, the internal stress generated by long-term oxidation and rust will aggravate the cracking of the panels, thereby affecting the safety and service life of the building. (4) In high humidity environments, especially in rainy seasons, ALC panels are prone to mildew and alkali efflorescence, which not only reduces the user experience but also increases the cost and complexity of subsequent maintenance. Summary of the invention

[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a method for preparing a fiber-reinforced autoclaved aerated concrete slab and its application. By using fibers to replace structural steel bars, the amount of steel bars used is saved, and steel bars will not be rusted due to cutting, thereby improving the slab yield and production efficiency, avoiding waste of waste, reducing costs, and improving actual preparation efficiency; secondly, by using fibers and active stimulants, the concrete slurry is gassed more evenly, and a multi-stage dispersion method is used to evenly distribute the fibers, effectively improving the bending resistance, compression resistance, crack resistance, nail holding force, mildew resistance and alkali resistance of the concrete slab, significantly improving product quality, and reducing later maintenance costs.

[0006] In order to achieve the above object, the present invention provides a method for preparing a fiber reinforced autoclaved aerated concrete board, comprising the following steps:

[0007] S1: Check that all equipment is operating normally and the raw materials meet the requirements, and prepare pre-treated sand, cement, quicklime, gypsum, fiber, aluminum powder, water and active activator according to the formula ratio;

[0008] S2: adding some water to the sand and gypsum, wet grinding and mixing to obtain slurry 1;

[0009] S3: adding cement, quicklime, fiber and active activator to the slurry 1, mixing and uniformly dispersing the fiber therein, to obtain slurry 2;

[0010] S4: mixing aluminum powder with part of water to prepare a suspension, adding the suspension to the second slurry, and mixing evenly to obtain a third slurry;

[0011] S5: heating the slurry to 40-45° C. by steam, and then pouring it into a mold for curing to form a green body, wherein the green body temperature is 70-90° C. during the curing process, and the curing time is 2-4 hours;

[0012] S6: turning over and demolding the formed green body in the mold, and cutting the green body according to the required product size;

[0013] S7: The cut green body is transported to an autoclave for curing. During the curing process, the temperature and pressure inside the autoclave are increased for 2 hours, so that the temperature inside the autoclave reaches 180-210°C and the pressure reaches 10-13MPa. After that, the temperature and pressure are kept constant for 6-10 hours, and then the temperature and pressure are reduced to normal temperature and pressure to produce the finished concrete slab.

[0014] Furthermore, in step S5, the mold is oiled before pouring.

[0015] Furthermore, in step S6, the waste generated during the cutting of the green body is peeled and stirred before being processed in step S5 together with the slurry 3.

[0016] Furthermore, the effective calcium oxide content in the quicklime should be >80%, the magnesium oxide content <5%, the undigested residue ≤8%, and meet the following performance indicators: digestion time >15min, digestion temperature >90°C, and initial heating time >5min.

[0017] Furthermore, in the cement: the CaO content is ≥60%, and the free CaO content is ≤1.5%; the NaCl and KCl contents are both less than 1.5%; the specific surface area is 250-350m 2 / kg; in the setting time parameters, the initial setting time is 1-3h and the final setting time is 3-6h;

[0018] The cement described is a single type of cement, not a composite cement.

[0019] Furthermore, the gypsum is desulfurized gypsum, and its main chemical component is CaSO 4 •2H 2 O content>70%.

[0020] Further, the fiber also includes at least one of modified PTFE fiber and modified basalt fiber, and the length is 0.1-20 mm;

[0021] The modification method includes: surface modification.

[0022] Furthermore, the aluminum powder has: a metallic aluminum content of >85%; an active aluminum content of >90%; a fineness standard of 3.0% or less of the residue passing through a 0.075 mm sieve hole; and a gas evolution rate of 50% or more in 4 minutes, 80% or more in 16 minutes, and 90% or more in 30 minutes.

[0023] Furthermore, the sodium butylnaphthalenesulfonate is in powder form, has a moisture content of ≤5%, and a pH value of 7-8.5 in a 1% aqueous solution.

[0024] Furthermore, the sulfamethoxazole is industrial grade sulfamethoxazole, and its purity is ≥98%.

[0025] Furthermore, the content of sodium dodecyl sulfate is ≥94%, and the pH value of the 1% aqueous solution is 7.5-9.5.

[0026] Furthermore, the polycarboxylate water reducer is in powder form, with a Cr content of ≤0.20%, NaSO 4 Content <4.0%, Na 2 O and K 2 The sum of O content is <2.0%, the fluidity of cement paste is ≥240mm, and the water reduction rate of mortar is >20%.

[0027] Furthermore, the main technical parameters of the graphite soil are: powder, particle size of 6-6.5µm, purity ≥95%.

[0028] Furthermore, fly ash is used to replace part of the sand to prepare the concrete slab, and the proportion of the sand replaced by the fly ash is 10-15 parts;

[0029] The fly ash is directly supplied for mixing through a pipeline conveying device, or is supplied for mixing after being made into slurry through wet ash discharge.

[0030] Furthermore, the concrete slab is prepared by partially or completely replacing the sand with solid waste;

[0031] The solid waste includes at least one of slag, steel slag, tailings and tailings mud.

[0032] Another aspect of the present invention provides an application of a fiber-reinforced autoclaved aerated concrete board, which is realized by applying the preparation method as described above. The concrete board is mainly a non-load-bearing wall of a building, including an inner wall and an outer wall.

[0033] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects compared with the prior art:

[0034] 1. The preparation method of the present invention uses fibers to replace structural steel bars, thereby saving steel bars and preventing steel bars from being rusted due to cutting, thereby improving the board yield and production efficiency, avoiding waste of waste materials, reducing costs, and improving actual preparation efficiency; secondly, by using fibers and active stimulants, the concrete slurry is gassed more evenly, thereby making the fibers evenly distributed, effectively improving the bending resistance, compression resistance, crack resistance, nail holding force, mildew resistance and alkali resistance of the concrete board, significantly improving product quality and reducing subsequent maintenance costs; in addition, by dispersing the fibers in multiple stages and evenly distributing them in the board, the compressive strength, bending strength and crack resistance of the board are effectively improved.

[0035] 2. The preparation method of the present invention controls the three temperatures of the slurry to be maintained at a certain temperature by steam, which can effectively ensure the workability of the slurry and provide an optimal environment for the subsequent gasification and hardening of the green body. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic flow chart of the steps of a method for preparing a fiber reinforced autoclaved aerated concrete board according to an embodiment of the present invention;

[0037] Figure 2 This is a flow chart of a method for preparing a fiber reinforced autoclaved aerated concrete board according to an embodiment of the present invention;

[0038] Figure 3 The surface conditions of the plates of the embodiments of the present invention and the comparative examples at the end of the test are shown.

[0039] In the attached Figure 3 In the comparative example 2, the result is Figure 3 a; Comparative Example 3 results are Figure 3 b; Example 8 results are Figure 3 c; Comparative Example 4 results are Figure 3 d. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0041] Example 1

[0042] As shown in the figure, Embodiment 1 of the present invention provides a method for preparing a fiber-reinforced autoclaved aerated concrete board, which is used to prepare a type of fiber-reinforced autoclaved aerated concrete board, comprising the following steps:

[0043] S1: Check that all equipment is operating normally and the raw materials meet the requirements, and prepare pre-treated sand, cement, quicklime, gypsum, fiber, aluminum powder, water and active activator according to the formula ratio;

[0044] S2: adding some water to the sand and gypsum, wet grinding and mixing to obtain slurry 1;

[0045] S3: adding cement, quicklime, fiber and active activator to the slurry 1, mixing and uniformly dispersing the fiber therein, to obtain slurry 2;

[0046] S4: mixing aluminum powder with part of water to prepare a suspension, adding the suspension to the second slurry, and mixing evenly to obtain a third slurry;

[0047] S5: heating the slurry to 40-45° C. by steam, and then pouring it into a mold for curing to form a green body, wherein the green body temperature is 70-90° C. during the curing process, and the curing time is 2-4 hours;

[0048] S6: turning over and demolding the formed green body in the mold, and cutting the green body according to the required product size;

[0049] S7: The cut green body is transported to an autoclave for curing. During the curing process, the temperature and pressure inside the autoclave are increased for 2 hours, so that the temperature inside the autoclave reaches 180-210°C and the pressure reaches 10-13MPa. After that, the temperature and pressure are kept constant for 6-10 hours, and then the temperature and pressure are reduced to normal temperature and pressure to produce the finished concrete slab.

[0050] Specifically, in step S1, the raw materials are composed of 10-15 parts of quicklime, 60-80 parts of sand, 3-5 parts of gypsum, 15-25 parts of cement, 0.25-0.5 parts of fiber, 0.04-0.1 parts of aluminum powder, 180-250 parts of water, and 0.1-0.25 parts of active stimulant by weight; the active stimulant is mainly composed of sodium butylnaphthalene sulfonate, sulfamethoxazole, sodium dodecyl sulfate, polycarboxylate water reducer and graphite, wherein, by weight, the raw materials are 8-10 parts of sodium butylnaphthalene sulfonate, 4-5 parts of sulfamethoxazole, 17-20 parts of sodium dodecyl sulfate, 6-8 parts of polycarboxylate water reducer, and 25-30 parts of graphite.

[0051] Preferably, the effective calcium oxide content in the quicklime should be >80%, the magnesium oxide content should be <5%, the undigested residue should be ≤8%, and the following performance indicators should be met: digestion time >15min, digestion temperature >90°C, and initial heating time >5min.

[0052] Preferably, the effective calcium oxide content in the quicklime is greater than 85%, thereby increasing the effective calcium content and reducing the product proportion dosage, which is used for cost control and product quality improvement;

[0053] The main technical parameters of the sand are shown in the following table:

[0054] Table 1: Main technical indicators of sand

[0055]

[0056] Table 2: Sand particle size distribution

[0057]

[0058] It should be noted that the purchased raw sand will be further processed after entering the factory to determine whether it meets the production requirements. The superior and first-class sands are treated the same way and no additional classification is required.

[0059] Preferably, the silicon content of the sand is ≥80%, which is used to improve the production quality of autoclaved aerated concrete blocks and panels;

[0060] The cement includes ordinary 42.5 grade silicate cement and meets the following technical requirements: CaO content is ≥60%, and the content of free CaO is ≤1.5%; the content of NaCl and KCl shall not exceed 1.5%; the specific surface area is 250-350m 2 / kg; in the setting time parameters, the initial setting time is 1-3h, and the final setting time is 3-6h; wherein the CaO content in the cement is ≥60%, and the free CaO content is ≤1.5%, which is used for cost control and product quality improvement;

[0061] Preferably, the cement is a single type of cement rather than a composite cement;

[0062] Preferably, the cement is used in the order in which it is put into storage, and the storage period of the cement should not exceed 3 months, and expired cement should be inspected;

[0063] The main chemical component of gypsum is CaSO 4 •2H 2 The content of O is >70%, which is used to regulate the gas generation process of aerated concrete. During the gas generation process of aluminum powder, the gas generation rate is controlled to avoid excessive gas generation leading to excessive or unstable bubbles, thereby affecting the pore structure and strength of concrete. It can also regulate the speed of quicklime digestion and slurry thickening.

[0064] Preferably, the gypsum is desulfurized gypsum to improve the strength and durability of the concrete slab.

[0065] Preferably, the fiber is at least one of modified PTFE (polytetrafluoroethylene fiber, Polytetrafluoroethylene Fiber) fiber and modified basalt fiber, and the modification method is surface modification. The specific modification method includes: soaking the pre-modified PTFE fiber and / or basalt fiber in a 5-15% sodium hydroxide solution at room temperature for 0.5-2 hours; washing the fiber soaked in sodium hydroxide with deionized water and anhydrous ethanol for multiple times until it is washed to neutral; adding the fiber washed to neutrality and γ-aminopropyl triethoxysilane coupling agent to the mixed solution of deionized water and anhydrous ethanol, stirring the mixed solution evenly and letting it stand; after standing, separating the fiber and the solution by filtering; the separated fiber and water-based epoxy resin are fully stirred and dried, and then cut into short fibers with a specification of 0.1-20mm to finally obtain modified fibers. It should be noted that the pre-modified PTFE fiber is a PTFE fiber that is filled and modified, and the filling material is glass fiber. It can be understood that when the fiber is only PTFE fiber, due to the alkali resistance of PTFE fiber and the absence of hydroxyl groups in its structure, the PTFE fiber surface impurities and static electricity are removed by washing with deionized water and anhydrous ethanol, and then wrapped with water-based epoxy resin to prevent it from agglomerating into flocculation, thereby helping to improve the performance of the autoclaved aerated concrete board prepared subsequently. In addition, in an optional embodiment, the PTFE fiber is pre-modified by a filling modification method, and the filling material is glass fiber. After that, the pre-modified PTFE fiber is processed by the surface modification preparation method to obtain a finished modified PTFE fiber, thereby further improving the performance of the autoclaved aerated concrete board by increasing the friction coefficient of the PTFE fiber.

[0066] It can be understood that by inserting the fibers into the concrete, a three-dimensional spatial structure is formed to absorb and disperse stress, thereby improving the compressive and tensile strengths of the board. Secondly, due to the short length of the fibers, they can be well dispersed in the concrete slurry and have good contact with the interface between the concrete particles, generating mechanical bite force. When the concrete board is subjected to external tension, the fibers can replace the board to bear a certain tension, thereby reducing the probability of cracks. Moreover, since the fibers are randomly distributed in the board, the fibers can evenly distribute the tension along the axial direction to the adjacent ones, thereby alleviating the concentration of stress and enhancing the toughness of the board. Thirdly, the fibers are randomly distributed in the board. The fibers are evenly distributed, which appropriately blocks the disordered growth rate of the autoclaved aerated concrete in the gas generation stage and inhibits the generation of large bubbles. At the same time, the thermal shrinkage performance of the fiber is similar to that of the substrate, which avoids the generation of air layers due to the shrinkage of the steel mesh in the traditional ALC board, making the pore structure of the board more dense and strong, and effectively improving the strength of the autoclaved aerated concrete product. In addition, by setting the final length of the fiber to 0.1-20mm, its fluidity in the concrete slurry can be effectively improved, so that it can be evenly distributed in the board. Secondly, it is avoided that the longer fibers are pulled out or broken during the cutting process, resulting in uneven incisions, increased burrs, and other phenomena that affect the quality of the cutting surface.

[0067] The aluminum powder can react with alkaline substances and water in the slurry to generate hydrogen during the sheet forming process, thereby improving the physical properties of the sheet. Its main technical parameters are: metal aluminum content>85%; active aluminum content>90%; fineness standard is the sieve residue passing through a 0.075mm sieve hole ≤3.0%; gas evolution rates are ≥50% in 4 minutes, ≥80% in 16 minutes, and ≥90% in 30 minutes;

[0068] The activity stimulant is mainly composed of sodium butylnaphthalene sulfonate, sulfamethoxazole, sodium dodecyl sulfate, polycarboxylic acid water reducer and graphite, wherein, by weight: 8-10 parts of sodium butylnaphthalene sulfonate, 4-5 parts of sulfamethoxazole, 17-20 parts of sodium dodecyl sulfate, 6-8 parts of polycarboxylic acid water reducer, 25-30 parts of graphite, and is used to improve the raw material activity, slurry workability, and gas hardening adaptability of the green body, effectively prevent the green body from settling and collapsing, and at the same time, optimize the water-cement ratio, the contact and mutual reaction between the fiber and the concrete particles, and enhance the final compressive strength of the product. In addition, the sulfamethoxazole used in the concrete board can effectively inhibit the mildew and alkali efflorescence of the board surface, especially in a rainy and humid environment.

[0069] The main technical parameters of the sodium butylnaphthalenesulfonate are: powdery, moisture content ≤5%, pH value of 7-8.5 in 1% aqueous solution.

[0070] The sulfamethoxazole is industrial grade sulfamethoxazole, and its main technical parameters are: melting point>160°C, density about 1.462g / cm 3, purity ≥98%. It should be noted that the molecular formula of sulfamethoxazole is C 10 H 11 N 3 O 3 S, with a molecular weight of 253.28 g / mol, contains a sulfonamide group (-SO 2 NH), a methoxazole ring (5-methyl-3-isoxazole), and a benzene ring. Due to its unique molecular structure, sulfamethoxazole has extremely low solubility in water, but can be dissolved in dilute sodium hydroxide solution and dilute acid. This property enables it to adapt well to the alkaline environment of concrete slurry and ensures uniform dispersion in the slurry, thereby more effectively exerting its function.

[0071] The main technical parameters of the sodium dodecyl sulfate are: melting point 180-207°C, density 0.25g / ml, sodium dodecyl sulfate content ≥94%, and pH value of 7.5-9.5 in 1% aqueous solution.

[0072] The main technical parameters of the polycarboxylate water reducer are: powder, Cr content ≤ 0.20%, NaSO 4 Content <4.0%, Na 2 O and K 2 The sum of O content is <2.0%, the fluidity of cement paste is ≥240mm, and the water reduction rate of mortar is >20%.

[0073] The main technical parameters of the graphite soil are: powder, particle size of 6-6.5µm, purity ≥95%, density 2-2.2g / cm³.

[0074] It should be noted that, because the autoclaved aerated concrete is loose and porous inside, it is called a "breathing board", but it also makes it easy to store water vapor in the air in the pores. When the water is not removed in time and it is used directly or in a high humidity environment, it is easy to cause alkali and mildew. The chemical structure of sulfamethoxazole consists of a p-aminobenzenesulfonamide group and a 5-methylisoxazole ring, wherein the cyclic amide group and the aromatic amine group can form a binary complex through the bond bridge effect with the metal cation, increase the adsorption capacity between the sulfamethoxazole molecule and the metal ion, and form sulfamethoxazole-heavy metal crystals; this process helps to lock the metal ions in the slurry, so that the metal ions in the board are evenly distributed, and because it is almost insoluble in water, it effectively prevents the diffusion of metal ions after the board is formed, thereby avoiding the occurrence of alkali; secondly, as a broad-spectrum antibiotic, sulfamethoxazole has a stable structure, can adapt to the processing environment of autoclaved aerated concrete boards, and can continue to produce toxic inhibition effects on bacteria and / or molds after the board is formed, thereby delaying the mildew of the concrete board.

[0075] Furthermore, the raw materials need to be pre-treated and measured to ensure that the raw materials meet the production requirements during the preparation process, thereby improving the preparation efficiency, which includes: the sand is crushed to a suitable size by ball milling and placed in a storage tank for standby use; the gypsum is slurried with water and placed in a storage tank for standby use; the quicklime is initially crushed and ball milled and placed in a warehouse for standby use.

[0076] Specifically, during the raw material mixing operation, the aluminum powder is added in step S4 to ensure that when the aluminum powder reacts with the alkaline substances and water in the slurry to generate hydrogen, the fibers in the board can be evenly dispersed.

[0077] Specifically, in step S5, the mold is oiled before pouring to facilitate the subsequent demoulding operation and ensure that the green body is completely ejected from the mold to avoid corner chipping or corner collapse during demoulding.

[0078] It should be noted that in step S5, the addition of the active stimulant can effectively shorten the green body gas hardening time by 25-30 minutes, thereby improving the adaptability of the production process and preventing the green body from settling and collapsing.

[0079] It should be noted that in step S5, the temperature of the slurry is maintained at a certain temperature by controlling the temperature of the slurry with steam, which can effectively ensure the workability of the slurry and provide an optimal environment for the subsequent gasification and hardening of the green body.

[0080] Specifically, in step S6, the waste generated during the cutting of the green body is peeled and stirred before being processed in step S5 together with the slurry 3 to improve the utilization rate of raw materials, avoid waste, and reduce production costs.

[0081] Furthermore, in step S7, the added active stimulant can effectively shorten the green body autoclave curing time by 2 hours, thereby shortening the process cycle and improving production efficiency.

[0082] Furthermore, according to the requirements of the final product, the finished concrete slab can be cut into fiber-reinforced autoclaved aerated concrete blocks and / or plates to adapt to the size of elevator transportation and be suitable for any construction site, thereby reducing the difficulty of transportation and secondary handling and improving handling efficiency; and since there is no steel mesh inside the concrete slab, the cutting efficiency is significantly improved and the production cost is reduced.

[0083] It should be noted that by mixing the fiber with the active activator, since the molecular structure of the polycarboxylate water-reducing agent in the active activator contains a large number of anionic and cationic strong polar groups, when these ions come into contact with the fiber surface, electrostatic repulsion can be generated, forming an organic adsorption layer on the fiber surface. This adsorption layer stretches in the solution like a comb, producing a steric hindrance effect, eliminating the ions generated on the fiber surface due to friction and other reasons, overcoming the problems of fiber floating and agglomeration in the slurry, and achieving the effect of dispersing the fiber; secondly, the water-based epoxy resin adhered to the surface of the fiber after surface modification is in the form of flakes and is heavy, so it is easy to sink in the slurry. , it is not easy to float in the slurry, therefore, compared with the unmodified fiber which is easy to aggregate into floccules, the modified fiber is easier to disperse in the slurry; in addition, during the pouring of step S5 and the steaming and curing of step S7, due to the high temperature and alkaline environment, the water-based epoxy resin on the outside of the uniformly dispersed modified fiber can be softened, and the modified fiber changes from sheet to floccules again, and the modified fiber after stirring is evenly distributed in the board, and the softened water-based epoxy resin can be evenly dispersed in the autoclaved aerated concrete board embryo, and at the same time, the polar hydroxyl and ether bonds contained in the epoxy resin molecular chain can be combined with concrete particles to form a strong chemical bond, thereby increasing the adhesion between the material and the concrete. It can be understood that by dispersing the fibers in multiple stages and evenly distributing them in the board, the compressive strength, bending strength and crack resistance of the board are effectively improved, and compared with the unmodified fibers, the length of the finished board is significantly increased, so as to meet various design requirements, especially the heightening design requirements, reduce the assembly construction of the board, and improve the construction efficiency. In addition, the preparation method is also applicable to preparing conventional fiber-reinforced autoclaved aerated concrete panels using unmodified fibers.

[0084] The preparation method of this embodiment generally includes: preparing pretreated raw materials according to a formula; distributing and mixing the raw materials evenly, and obtaining slurry one, slurry two and slurry three in sequence; pouring slurry three into a mold and then curing it; demolding and cutting the blank; preparing a finished concrete slab after steaming and cooling the blank after cutting; using fibers to replace structural steel bars, saving steel bars, so that steel bars will not be corroded due to cutting, thereby improving the slab yield and production efficiency, avoiding waste, reducing costs, and improving actual preparation efficiency; secondly, by using modified fibers and active stimulants, the concrete slurry is gasified more evenly, and a multi-stage dispersion method is used to evenly distribute the fibers, effectively improving the bending resistance, compression resistance, crack resistance, nail holding force, mildew resistance and anti-alkali performance of the concrete slab, significantly improving product quality, and reducing later maintenance costs.

[0085] Example 2

[0086] On the basis of Example 1, in Example 2 of the present invention, fly ash is used to replace part of the sand to prepare the concrete slab, and the number of sand replaced by the fly ash is 10-15 parts, which is used to reduce costs and increase efficiency while ensuring that the quality of the concrete slab meets the requirements, thereby improving the competitiveness of the enterprise.

[0087] Preferably, the main technical indicators of the fly ash are as follows:

[0088] Table 3: Main technical indicators of fly ash

[0089]

[0090] Preferably, the fly ash is directly supplied for mixing through a pipeline conveying device, or is made into a slurry through wet ash discharge and then supplied for mixing. It should be noted that when wet ash discharge is used, the water content and water weight in the wet ash need to be calculated, and the amount of water in the original components needs to be reduced.

[0091] Example 3

[0092] Based on Example 1, in Example 3 of the present invention, solid waste is used to partially or completely replace the sand to prepare the concrete slab, which is used to reduce the consumption of natural resources while ensuring that the quality of the concrete slab meets the requirements, and is helpful to process a large amount of industrial solid waste, reduce the pressure on landfills and the risk of environmental pollution, reduce costs and increase efficiency, and enhance corporate competitiveness.

[0093] Preferably, the solid waste includes at least one of slag, steel slag, tailings and tailings mud.

[0094] Example 4

[0095] On the basis of Examples 1 to 3, Example 4 of the present invention provides an application of a method for preparing a fiber-reinforced autoclaved aerated concrete slab, wherein the prepared concrete slab is mainly a non-load-bearing wall of a building, including interior walls and exterior walls.

[0096] Example 5

[0097] On the basis of Example 1, Example 5 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 62 parts of sand, 4 parts of gypsum, 18 parts of cement, 0.25 parts of fiber, 0.05 parts of aluminum powder, 180 parts of water, and 0.125 parts of active activator.

[0098] Example 6

[0099] Based on Example 1, Example 6 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 15 parts of quicklime, 60 parts of sand, 5 parts of gypsum, 20 parts of cement, 0.3 parts of fiber, 0.055 parts of aluminum powder, 190 parts of water, and 0.1 parts of an active stimulant.

[0100] Example 7

[0101] Based on Example 1, Example 7 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 15 parts of quicklime, 80 parts of sand, 3 parts of gypsum, 21 parts of cement, 0.4 parts of fiber, 0.06 parts of aluminum powder, 210 parts of water, and 0.2 parts of active activator.

[0102] Example 8

[0103] On the basis of Example 1, Example 8 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of active activator.

[0104] Comparative Example 1

[0105] On the basis of Example 1, Comparative Example 1 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are calculated by weight as follows:

[0106] 15 parts of quicklime, 80 parts of sand, 3 parts of gypsum, 21 parts of cement, 0.4 parts of fiber, 0.06 parts of aluminum powder, and 180 parts of water.

[0107] In the autoclaved aerated concrete boards in Examples 5 to 8, the fibers used are modified fibers, and the active activator is a mixed material from the same batch, and these raw materials are calculated by weight: 9 parts of sodium butylnaphthalene sulfonate, 5 parts of sulfamethoxazole, 18 parts of sodium dodecyl sulfate, 6 parts of polycarboxylate water reducer, and 25 parts of graphite clay; secondly, the sizes of the finished autoclaved aerated concrete boards prepared in Examples 5 to 8 and Comparative Example 1 are all 1800mm×600mm×100mm. At the same time, the basic properties of each concrete board were tested in the laboratory using standard test methods, and the test results are shown in Table 4:

[0108] Table 4: Test results of the first batch of concrete slab samples

[0109]

[0110] It can be seen from the test results in Table 4 that the concrete slabs in the above-mentioned Examples 6 to 8 all meet the requirements for concrete slabs in national and / or industry standards, and can fully meet the various performance requirements of non-load-bearing walls of buildings, but the drying shrinkage values ​​of the samples in Example 5 and Comparative Example 1 exceed the standard values. In particular, the concrete slabs in the four embodiments to which the active stimulant is added are significantly better than Comparative Example 1 to which the active stimulant is not added in terms of compressive strength; secondly, the addition of the active stimulant significantly improves the contribution of the fiber to the bending bearing capacity of the concrete slab. In addition, the concrete slab of Example 8 is better than the other three embodiments in both the maximum and minimum values ​​of compressive strength, which is related to the higher proportions of sand, cement, quicklime, fiber and active stimulant in its formula. This result shows that increasing the amount of active stimulant can further promote the contact and interaction between the fiber and concrete particles, thereby effectively improving the performance of the concrete slab.

[0111] Example 9

[0112] On the basis of Example 1, Example 9 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;

[0113] Among them, the mixed materials in the active stimulant are as follows: 10 parts of sodium butylnaphthalene sulfonate, 5 parts of sulfamethoxazole, 20 parts of sodium dodecyl sulfate, 6 parts of polycarboxylic acid water reducer, and 30 parts of graphite clay.

[0114] Example 10

[0115] On the basis of Example 1, Example 10 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;

[0116] Among them, the mixed materials in the active stimulant are as follows: 9 parts of sodium butylnaphthalene sulfonate, 4 parts of sulfamethoxazole, 17 parts of sodium dodecyl sulfate, 7 parts of polycarboxylic acid water reducer, and 27 parts of graphite clay.

[0117] Embodiment 11

[0118] On the basis of Example 1, Example 11 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;

[0119] Among them, the mixed materials in the active stimulant are: 8 parts of sodium butylnaphthalene sulfonate, 5 parts of sulfamethoxazole, 19 parts of sodium dodecyl sulfate, 8 parts of polycarboxylic acid water reducer, and 25 parts of graphite clay.

[0120] Among them, the finished autoclaved aerated concrete panels prepared in the above Examples 8 to 11 and Comparative Example 1 have a size of 1800 mm×600 mm×100 mm, and the fibers are all modified fibers. At the same time, the basic properties of each concrete panel were tested in the laboratory using standard test methods. The test results are shown in Table 5:

[0121] Table 5: Test results of the second batch of concrete slab samples

[0122]

[0123] It can be seen from the test results in Table 5 that the concrete slabs in the above four embodiments all meet the requirements for concrete slabs in national and / or industry standards, and can fully meet the various performance requirements of non-load-bearing walls of buildings. In particular, taking Example 8 as a reference, by adjusting the ratio of the mixed materials in the active stimulant, the compressive strength of the concrete slabs of Examples 9 to 11 obtained is significantly higher than that of Comparative Example 1 to which no active stimulant is added. In addition, the differences between the performance parameters of the above four embodiments are not significant, which means that the different mixed material ratios of the active stimulants used in the experiment can effectively improve the performance of the concrete slabs, showing good adaptability and consistency. These results further confirm the important role and flexibility of active stimulants in improving the performance of concrete slabs.

[0124] Comparative Example 2

[0125] On the basis of Example 1, Comparative Example 2 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;

[0126] The mixed materials in the active stimulant are as follows: 9 parts of sodium butylnaphthalene sulfonate, 0 parts of sulfamethoxazole, 18 parts of sodium dodecyl sulfate, 6 parts of polycarboxylic acid water reducer, and 25 parts of graphite clay.

[0127] Comparative Example 3

[0128] On the basis of Example 1, Comparative Example 3 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;

[0129] Among them, the mixed materials in the active stimulant are as follows: 9 parts of sodium butylnaphthalene sulfonate, 2 parts of sulfamethoxazole, 18 parts of sodium dodecyl sulfate, 6 parts of polycarboxylic acid water reducer, and 25 parts of graphite clay.

[0130] Comparative Example 4

[0131] On the basis of Example 1, Comparative Example 4 of the present invention provides a fiber-reinforced autoclaved aerated concrete board, which is prepared by the preparation method in Example 1, wherein the raw materials in the concrete board are, by weight: 13 parts of quicklime, 67 parts of sand, 3 parts of gypsum, 17 parts of cement, 0.5 parts of fiber, 0.045 parts of aluminum powder, 180 parts of water, and 0.25 parts of an active activator;

[0132] Among them, the mixed materials in the active stimulant are as follows: 9 parts of sodium butylnaphthalene sulfonate, 8 parts of sulfamethoxazole, 18 parts of sodium dodecyl sulfate, 6 parts of polycarboxylic acid water reducer, and 25 parts of graphite clay.

[0133] Among them, the concrete boards prepared in the above comparative examples 2 to 4 and Example 8 are all modified fibers, and the board size is 1800mm×600mm×100mm. Afterwards, the whole board is cut into test sample blocks of 200mm×100mm×100mm, and the sample blocks of the above embodiments and comparative examples are placed at 30°C and a relative humidity of 90% for 60 days, and the mildew and alkali efflorescence of each sample block are observed and recorded, wherein the initial mildew time is the initial days when mildew appears on the board surface, and the initial alkali efflorescence time is the initial days when white crystals appear on the board surface. The test results are shown in Tables 6 and Figure 3 (Comparative Example 2 results are Figure 3 a; Comparative Example 3 results are Figure 3 b; Example 8 results are Figure 3 c; Comparative Example 4 results are Figure 3 d):

[0134] Table 6: Test results of the third batch of concrete slab samples

[0135]

[0136] It can be seen from the test results in Table 6 that the sample blocks of the comparative example 2 group without sulfamethoxazole added showed mildew on the 3rd day and alkali efflorescence on the 30th day under the test conditions, and the alkali efflorescence on the surface of the sample blocks was serious when the test was stopped; the sample blocks of the comparative example 3 group with low dosage of sulfamethoxazole showed mildew on the 7th day and alkali efflorescence on the 45th day; while the sample blocks of the example 8 group with medium dosage and the sample blocks of the comparative example 4 group with high dosage both showed mildew on the 20th day, and no alkali efflorescence occurred during the test period; the above test results show that sulfamethoxazole can effectively inhibit the mildew and alkali efflorescence of the concrete slab and the effect is positively correlated with its addition amount, but when the addition amount reaches a certain amount, the effect has no significant difference, therefore, the sulfamethoxazole in the concrete slab can be appropriately adjusted according to the amount of other metal-containing raw materials to reduce the production cost.

[0137] It should be noted that in the present invention, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "includes..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Those skilled in the art will readily understand that the above are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. A method for preparing a fiber-reinforced autoclaved aerated concrete board, characterized in that: The steps include: S1: Check that all equipment is operating normally and the raw materials meet the requirements, and prepare pre-treated sand, cement, quicklime, gypsum, fiber, aluminum powder, water and active activator according to the formula ratio; the active activator is mainly composed of sodium butylnaphthalene sulfonate, sulfamethoxazole, sodium dodecyl sulfate, polycarboxylate water reducer and graphite clay; S2: adding some water to the sand and gypsum, wet grinding and mixing to obtain slurry 1; S3: adding cement, quicklime, fiber and active activator to the slurry 1, mixing and uniformly dispersing the fiber therein, to obtain slurry 2; S4: mixing aluminum powder with part of water to prepare a suspension, adding the suspension to the second slurry, and mixing evenly to obtain a third slurry; S5: heating the slurry to 40-45° C. by steam, and then pouring it into a mold for curing to form a green body, wherein the green body temperature is 70-90° C. during the curing process, and the curing time is 2-4 hours; S6: turning over and demolding the formed blank in the mold, and cutting the blank according to the required product size; S7: The cut green body is transported to an autoclave for curing. During the curing process, the temperature and pressure inside the autoclave are increased for 2 hours, so that the temperature inside the autoclave reaches 180-210°C and the pressure reaches 10-13MPa. After that, the temperature and pressure are kept constant for 6-10 hours, and then the temperature and pressure are reduced to normal temperature and pressure to produce the finished concrete slab.

2. The preparation method according to claim 1, characterized in that: In step S5, the mold is oiled before pouring.

3. The preparation method according to claim 1, characterized in that: In step S6, the waste generated during the cutting of the green body is peeled and stirred before being processed with the slurry 3 in step S5.

4. The preparation method according to claim 1, characterized in that: The quicklime should have an effective calcium oxide content of >80%, a magnesium oxide content of <5%, undigested residue ≤8%, and meet the following performance indicators: digestion time greater than 15 minutes, digestion temperature >90°C, and initial heating time >5 minutes.

5. The preparation method according to claim 1, characterized in that: The cement has a CaO content of ≥60% and a free CaO content of ≤1.5%; the NaCl and KCl contents are both less than 1.5%; and a specific surface area of ​​250-350m 2 / kg; in the setting time parameters, the initial setting time is 1-3h and the final setting time is 3-6h; The cement described is a single type of cement, not a composite cement.

6. The preparation method according to claim 1, characterized in that: The gypsum is desulfurized gypsum, and the content of the main chemical component CaSO4•2H2O is >70%.

7. The preparation method according to claim 1, characterized in that: The fiber comprises at least one of modified PTFE fiber and modified basalt fiber, and has a length of 0.1-20 mm; The modification method includes: surface modification.

8. The preparation method according to claim 1, characterized in that: The aluminum powder has: a metal aluminum content of >85%; an active aluminum content of >90%; a fineness standard of 3.0% or less of the residue passing through a 0.075 mm sieve hole; and gas evolution rates of 50% or more in 4 minutes, 80% or more in 16 minutes, and 90% or more in 30 minutes.

9. The preparation method according to claim 1, characterized in that: The sodium butylnaphthalenesulfonate is in powder form, with a moisture content of ≤5% and a pH value of 7-8.5 in a 1% aqueous solution.

10. The preparation method according to claim 9, characterized in that: The sulfamethoxazole is industrial grade sulfamethoxazole, and its purity is ≥98%.

11. The preparation method according to claim 10, characterized in that: The sodium dodecyl sulfate has a content of ≥94% and a pH value of 7.5-9.5 in a 1% aqueous solution.

12. The preparation method according to claim 11, characterized in that: The polycarboxylate water-reducing agent is in powder form, with a Cr content of ≤0.20%, a NaSO4 content of <4.0%, a sum of Na2O and K2O contents of <2.0%, a cement paste fluidity of ≥240 mm, and a mortar water reduction rate of >20%.

13. The preparation method according to claim 12, characterized in that: The main technical parameters of the graphite soil are: powder, particle size of 6-6.5µm, purity ≥95%.

14. The preparation method according to any one of claims 1 to 13, characterized in that: The concrete slab is prepared by replacing part of the sand with fly ash, and the amount of the sand replaced by the fly ash is 10-15 parts; The fly ash is directly supplied for mixing through a pipeline conveying device, or is supplied for mixing after being made into slurry through wet ash discharge.

15. The preparation method according to any one of claims 1 to 13, characterized in that: Using solid waste to partially or completely replace the sand to prepare the concrete slab; The solid waste includes at least one of slag, steel slag, tailings and tailings mud.

16. An application of a fiber reinforced autoclaved aerated concrete board, which is realized by applying the preparation method according to any one of claims 1 to 15, characterized in that: The concrete slabs are mainly non-load-bearing walls of buildings, including interior walls and exterior walls.

Citation Information

Patent Citations

  • Autoclaved aerated concrete slab with built-in truss steel bars

    CN215167134U

  • Method for preparing concrete water reducing agent

    CN105800986A

  • Antibacterial mortar and preparation method thereof

    CN107793086A